Rules for the design construction and inspection of offshore structures (Hovik, Norway : Det Norske Veritas, 1977)
App. C: steel structure -- app. D: concrete structures -- app. E: Hydrostatic stability and anchoring -- app. F: Foundations -- app. G : Dynamic analysis -- app. I : in service inspection -- app. J : Documentation